2020
DOI: 10.1002/mgg3.1302
|View full text |Cite
|
Sign up to set email alerts
|

Medulloblastoma, macrocephaly, and a pathogenic germline PTEN variant: Cause or coincidence?

Abstract: Background Medulloblastomas (MBs) are a heterogeneous group of childhood brain tumors with four consensus subgroups, namely MBSHH, MBWNT, MBGroup 3, and MBGroup 4, representing the second most common type of pediatric brain cancer after high‐grade gliomas. They suffer from a high prevalence of genetic predisposition with up to 20% of MBSHH caused by germline mutations in only six genes. However, the spectrum of germline mutations in MBSHH remains incomplete. Methods Comprehensive Next‐Generation Sequencing pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…PTEN-ASD patients manifested a greater severity of cognitive deficits in comparison with PTENwt ASD patients [15]. On the other hand, while the core ASD symptoms are similar in both PHTS and…”
Section: Autism Spectrum Disordermentioning
confidence: 84%
See 2 more Smart Citations
“…PTEN-ASD patients manifested a greater severity of cognitive deficits in comparison with PTENwt ASD patients [15]. On the other hand, while the core ASD symptoms are similar in both PHTS and…”
Section: Autism Spectrum Disordermentioning
confidence: 84%
“…PTEN ‐ASD patients manifested a greater severity of cognitive deficits in comparison with PTEN wt ASD patients [15]. On the other hand, while the core ASD symptoms are similar in both PHTS and PTEN wt ASD with concurrent macrocephaly, PTEN ‐correlated ASD showed lower clinical ratings of autism severity as well as more sensory abnormalities compared to the sporadic disorder.…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that phosphatase and tensin homolog deleted on chromosome 10 (PTEN) dysfunction plays a crucial role in the development and progression MB. PTEN plays important roles in many cellular processes, including cell-cycle progression and apoptosis (Tolonen et al, 2020). Li et al (2015) reported the upregulation of miR-106b in MB.…”
Section: Medulloblastomamentioning
confidence: 99%
“…Recently, it has been shown that the SHH subgroup is most frequently (approximately 20–40%) associated with germline mutations ( BRCA2 , PALB2 , PTCH1 , SUFU , and TP53 ; Waszak et al, 2018 ; Garcia-Lopez et al, 2021 ). Currently, MB cases are rarely described in individuals with Cowden syndrome ( Waszak et al, 2018 ; Tolonen et al, 2020 ), a condition included in the PHTS spectrum. Instead, cases associated with other CNS tumors such as dysplastic gangliocytoma, meningioma, pineal tumor, oligodendroglioma, and glioblastoma have been reported in patients with this condition ( Kim et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%